Online Based Learning on Family Medicine Module for Medical Student: A Case Study on Postpartum Depression and Child Neglect - Savitri, Myrna D.; Najmuddin, Naufal; Karimah, Azimatul (Faculty of Medicine, Universitas Airlangga, 2022)
Family medicine is one branch of medical field that provides a holistic care to ailments in every age group. Medical student need to fully understand family medicine by using holistic approach to an illness. Pandemic restrictions make movie watching as an alternative in remote learning. This study aims to take cases from movies and asses the management of patient using family medicine approach. We herein report and study the case reviewed from a web-series in which an infant was abandoned by her mother who suffers from postpartum depression. We highlight on the accuracy of the portrayal of the disorder and also assessing the steps taken by healthcare worker to treat the patient as a whole to determine the validity of using movie as a learning tool for medical student.